Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7150/thno.33876
|View full text |Cite|
|
Sign up to set email alerts
|

Focused ultrasound activates voltage-gated calcium channels through depolarizing TRPC1 sodium currents in kidney and skeletal muscle

Abstract: Pulsed focused ultrasound (pFUS) technology is being developed for clinical neuro/immune modulation and regenerative medicine. Biological signal transduction of pFUS forces can require mechanosensitive or voltage-gated plasma membrane ion channels. Previous studies suggested pFUS is capable of activating either channel type, but their mechanistic relationship remains ambiguous. We demonstrated pFUS bioeffects increased mesenchymal stem cell tropism (MSC) by altering molecular microenvironments through cyclooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 68 publications
2
44
1
1
Order By: Relevance
“…This result is in contrast with previous studies that identified an important role for cytoskeletal networks in transducing US stimuli (De Cock et al, 2015). An important difference between our high frequency non-contact focused US stimulus and most other studies is that the latter uses low frequency US and requires physical contact with the PM through microbubbles (Burks et al, 2019;Carreras-Sureda et al, 2018;Clapham, 2007). This could explain why an intact cytoskeleton appeared necessary for internal Ca 2+ release in these other studies.…”
Section: Fus-dependent Ca 2+ Oscillatory Response Does Not Depend On contrasting
confidence: 95%
See 2 more Smart Citations
“…This result is in contrast with previous studies that identified an important role for cytoskeletal networks in transducing US stimuli (De Cock et al, 2015). An important difference between our high frequency non-contact focused US stimulus and most other studies is that the latter uses low frequency US and requires physical contact with the PM through microbubbles (Burks et al, 2019;Carreras-Sureda et al, 2018;Clapham, 2007). This could explain why an intact cytoskeleton appeared necessary for internal Ca 2+ release in these other studies.…”
Section: Fus-dependent Ca 2+ Oscillatory Response Does Not Depend On contrasting
confidence: 95%
“…This raised the possibility that an internal mechanosensory event is present and coupled to Ca 2+ release from an internal storage site. Other work has also identified an ER dependent Ca 2+ response mechanism using more conventional US stimulation involving IP3R activation (Burks et al, 2019). This response required an intact cytoskeleton believed to be important for the mechanotransduction of the stimulus to the ER membrane localized IP3R .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Future studies will need to examine specific mechanisms of DNA damage by pFUS, which could include generation of reactive oxygen species (ROS) through pFUS-induced cytosolic Ca 2+ fluxes [57]. We have demonstrated that pFUS generates Ca 2+ transients by activating mechanically sensitive ion channels in the plasma membrane, which leads to depolarization of voltage-gated calcium channels [58]. While these exposures did not generate cavitation forces, intracellular Ca 2+ fluxes have also been reported from inertial cavitation mechanical forces [59].…”
Section: Discussionmentioning
confidence: 99%
“…Specific microenvironmental changes resulting from mechanotransduction of US have received substantial attention, yet it remains unclear how the mechanical effects of US interact with tissues elicit these molecular responses. We previously demonstrated in skeletal muscle and kidney that pFUS at the above parameters mechanically activates the transient receptor potential channel 1 (TRPC1), which subsequently activates voltage gated calcium channels to initiate a calcium-dependent increase in COX2 expression (Burks et al, 2019). At those pFUS parameters, formation and cavitation of bubbles from dissolved tissue gases was not detected and viscoelastic modeling suggested that tissue deformations generated by acoustic radiation forces (ARF) were sufficient to increase COX2.…”
Section: Introductionmentioning
confidence: 99%